Yantramanav: A 8 DOF Bipedal Walking Robot – A Developmental Design - Malla, Samrat; Sharan, Raju; Shrestha, Subham; Pant, Yuv Raj; Dahal, Suramya Sharma (KEC Journal of Science and Engineering, 2023)
This paper proposes a study on development design of bipedal walking robot. A bipedal walking robot is a type of humanoid robot which mimics the walking of human beings and can be programmed to perform specific tasks as required. In this paper we present the building of a robot that provides physical locomotion such as walking, climbing stairs, etc. along with providing live video feedback to the user. Our bipedal robot is constructed by 8 motors and it has one DOF (degree of freedom) in each joint. This paper also describes how the bipedal robot is built, how the movement steps are obtained and how fall detection mechanism is implemented. To maintain the real time balanced locomotion and to measure the stability performance of the robot, an accelerometer and gyroscope sensor and foot pressure sensors are used. The movement of the robot can be controlled by using a remote controller. This bipedal robot can assist humans to carry out surveillance in hazardous environments like mines, fire, natural disaster etc. This greatly helps the rescue process during disasters and accidents.